How to do everything iCloud - Rich, Jason R. (New York McGraw-Hill Education, 2014)
"Maximize the latest iCloud capabilities. This all-new edition of How To Do Everything : iCloud fully covers iCloud's versatile features and offers step-by-step directions on how to use each one, including Shared Photo Streams, the iWork for iCloud apps, and iCloud Keychain. You'll learn how to set up iCloud, transfer and sync app-specific data, documents, files, photos, music, and other content among your computers and iOS mobile devices; use iCloud with your Mac, iPhone, iPad, iPad mini, and iPod touch; migrate from Apple MobileMe to iCloud; learn new iCloud features, including Shared Photo Streams, iWork for iCloud online apps, iCloud Keychain, and much more; manage your digital music library and iTunes purchases with iCloud; use the Premium iTunes Match service; store and manage your digital photos with My Photo Stream; share your digital images with others using iCloud's Shared Photo Streams; sync files and documents among computers and iOS devices; manage and sync your Safari bookmarks, reading list, and passwords using iCloud and iCloud Keychain; work with iWork for iCloud; learn about other cloud-based services Sync and share apps, app-related data, and eBooks among iOS mobile devices and your computer(s); back up your iPhone and iPad with iCloud Stream Apple TV content to your HD TV; locate a Lost Mac, iPhone, iPad or iPod touch with iCloud's Find My... feature; manage your iCloud email account; troubleshoot iCloud-related problems"--Provided by publisher.
Introduction -- Part I. Learn About Online File Sharing and Apple's iCloud -- Chapter 1 Learn About Cloud-Based Online File Sharing Services -- Chapter 2 How Mac Users Can Utilize iCloud -- Chapter 3 How iPhone, iPad, iPad mini and iPod Touch Users Can Utilize iCloud -- Chapter 4 New OS X Mavericks and iOS 7 iCloud Features and How To Utilize Them -- Part II. Manage Your Music, Multimedia Content and Photos in the Cloud -- Chapter 5 Manage Your Digital Music Library and iTunes Purchases with iCloud -- Chapter 6 Use the Premium iTunes Match Service -- Chapter 7 Use iCloud to Store and Manage Your Digital Photos with Photo Stream -- Chapter 8 Share Your Digital Images With Others Using iCloud Shared Photo Stream -- Part III. Share Documents, Music, Data and More via iCloud and Other Services -- Chapter 9 Manage & Sync Your Safari Bookmarks, Reading List and Passwords Using iCloud and Keychain -- Chapter 10 Working With iWork for iCloud -- Chapter 11 Cloud-Based File/Document Sharing Alternatives To iCloud -- Chapter 12 Share Documents, Files and App-Specific Data with iCloud -- Chapter 13 Cloud-Based Music & Video Streaming Service Alternatives To iCloud -- Part IV. Use iCloud With Your iPhone and iPad Running iOS 7 (or Later) -- Chapter 14 Manage Apps, App-Related Data and eBooks with iCloud -- Chapter 15 Back Up Your iPhone or iPad with iCloud -- Chapter 16 iCloud and Apple TV : The Perfect Entertainment Combination -- Part V: Additional iCloud Features and Functions -- Chapter 17 Locate a Lost Mac, iPhone, iPad or iPod Touch with iCloud's Find My... Feature -- Chapter 18 Manage Your iCloud Email Account -- Appendix A. Troubleshoot iCloud-Related Problems.
Keywords: iCloud; Cloud computing; Apple computer